ASEAN SYNERGY TO OVERCOME CHALLENGES IN INVESTMENT ARBITRATION - Herliana, Herliana (UI Scholars Hub, 2015)
Cambodia, Indonesia, Lao, Malaysia, Thailand, and the Philippines, have been sued by foreign investors through international investment arbitrations (IIA). No matter whether the outcome is favorable or not, those countries have spend significant time, energy, and financial resources to arbitrate. ASEAN countries are not in advantageous position in IIA.The first and the most obvious reason is language barrier. Arbitration proceedins are mainly conducted in English. Consequently, the arbitrators and counsels more often than not come from English speaking countries. Not only do they lead to high cost, but also they lack of familiarity with South East Asia’s social, politics, economic, culture and customs. This may influence how they treat the cases such as the interpretation of provisions specifically designed to protect foreign investors such as: national treatment; fair and equitable treatment; most favored nation; and also in deciding jurisdictional issues. regional news as a legal basis for foreign investment activities aim to provide protection for foreign investor. On the other hand, it also serves as a mean to facilitate economic development in the host states of investment. Unfortunately, BITs often contain excessive and limitless protection clauses in order to attract foreign investors. This may endanger host states position as it can be used as a weapon by the investors to sue the host states. In responding to this fact, it is necessary to strengthen cooperation among ASEAN members in dealing with foreign investors through BIT. The ideal picture will be that SEA is pro-market and pro-arbitration reform. It is unavoidable that in order to protect themselves from harsh investors as well as intricate arbitration, ASEAN would be better off having its own investment arbitration center run by its experts. Thus, the short-term challenge is to equip legal practitioners, business players and academicians with more knowledge, skills and experiences in dealing with investment disputes. The long-term step will be to negotiate model of investment treaties applicable in the region and to harmonize national investment laws. These efforts are strategic opportunities for ASEAN as single market to keep balance between promoting investment, protecting investors and the host states at the same time.